Digital Transformation in Public Administration through Digital Leadership to Improve Government Efficiency - Muhtarom Muhtarom; Untung Rahardja; Po Abas Sunarya; Arthur Freeman (Technomedia Journal, 2026)
This study examines the role of digital leadership in accelerating digital transformation within public administration to improve governmental efficiency. The objective of this research is to analyze how digital leadership influences the effectiveness, transparency, and service quality of public sector institutions in the digital era. This study employs a quantitative approach using survey data collected from 125 public sector employees, complemented by Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test the relationships between variables. The results indicate that digital leadership has a significant positive effect on the success of digital transformation initiatives, which in turn enhances operational efficiency, decision-making speed, and public service delivery quality additionally, organizational readiness and technological infrastructure are identified as supporting factors that strengthen these relationships. In conclusion, the study highlights that effective digital leadership is a critical driver in ensuring successful digital transformation in public administration, thereby improving overall government performance, and it is recommended that policymakers invest in leadership development and digital capability enhancement to sustain long-term efficiency gains.